Studi Kualitatif Pola Asuh Makan dan Status Gizi Balita dengan Orang Tua Tunarungu pada Komunitas Pengajian Tunarungu di Wonokromo, Surabaya - Fourynisa Maretta Fathurrizky; Choirul Anna Nur Afifah (Media Gizi Kesmas, 2024)
Background: Toddlers experience rapid physical and psychomotorical growth and development. Toddler nutritional status, which is influenced by feeding patterns, is one of the indicators of the toddler’s health. Feeding patterns are part of parenting. It is also an interaction between parents and toddlers, including deaf parents. The limited ability to hear impedes the language and communication skills of deaf, so it has an impact to the way deaf parents raise their toddlers. Objectives: This study aimed to examine parenting patterns and the nutritional status of toddlers from deaf parents in the deaf recitation community in Wonokromo Village, Surabaya. Method: Interviews, observations, documentation, and anthropometric measurements were held on three deaf families selected through purposive sampling. Family members and health workers were interviewed for data triangulation. The data were analyzed by grouping data according to themes in narratives. Results: The results showed that two mothers had not breastfed for even two years. Deaf mothers found it difficult to breastfeed while working. Toddlers who live with families know and accept more types of food. Deaf parents share roles in providing food, so mothers are not the main providers. Deaf parents follow the toddler's wishes and do not force them to eat. Deaf parents act as providers while the toddlers are the receiver. Toddlers were not given choices in their food menu, were fed, and were allowed to play, so they did not focus on their food. Deafness also affect on the lack of nutritional knowledge due to limited understanding, access to information, and communication. The three toddlers showed normal nutritional status at the time of the study. Although, one of the toddlers showed underweight status before the study. Conclusion: Deafness is not a big obstacle in toddlers' feeding patterns. However, it still impacting the feeding practice, especially in the introduction of food. This research also shows the principal role of families and health workers as supervisors, information providers, and motivators, especially in monitoring the growth of toddlers whose parents are deaf. The nutritional status of the three toddlers showed normal by the antropomethric measurements.